Distribution into the quadrupole mass filter with round rods. - Kashanian, F.; Nouri, S.; Chaharborj, S. Seddighi; Abu Bakar, Mohd Rizam (Elsevier, 2011)
Potential field distribution of a quadrupole mass filter with circular cross-section electrodes is described. At first, using superposition principle, we calculate potential around a round rod which is subjected to a given potential. By standard separation method, we then able to obtain the potential distribution into the quadrupole mass filter with circular rods. The results are compared with those obtained with a conventional hyperbolic rod set. Also, the results show that, for the same equivalent operating point in two stability diagrams (having the same βy) the associated modulated secular ion frequencies behavior are the same.